Models and solutions for emergency logistics - Yi, Wei (2008)
Emergency logistics planning is increasingly becoming a crucial issue due to the increase in the occurrence of natural disasters and other crisis situations. An adequate level of mitigation measures and a coordinated post-disaster relief logistics management may help to reduce the loss of both human lives and economic damage. Logistics planning in emergencies involves dispatching commodities to affected areas and evacuation of wounded people to emergency units. The number of vehicles involved may be very large during on-going relief operations. Furthermore, time plays a critical role in the logistic plan, and it directly affects the survival rate in affected areas. This makes the task of logistics planning more complex than conventional distribution problems.